Rothia aeria vertebral discitis/osteomyelitis in an immunocompetent adult: Case report and literature review. (2022) - Sewell, J.; Sathish, R.; Epa, D. Seneviratne; Lewicki, M.; Amos, L.; Teh, E.; Popp, L.; Jaw, J.; Davis, G.A.; Chin, R.
Abstract: Rothia aeria is a gram-positive, pleomorphic bacteria forming part of human oral microflora usually only causing periodontal and dental infections. We describe the case of a 68-year-old immunocompetent male with lumbar vertebral discitis/osteomyelitis caused by R. aeria . A review of the literature demonstrated seventeen cases of non-dental R. aeria infection of which only six were in immunocompetent individuals. This is the first reported case of R. aeria vertebral discitis/osteomyelitis.